2006
DOI: 10.1177/1077801206294115
|View full text |Cite
|
Sign up to set email alerts
|

Community Violence and Its Direct, Indirect, and Mediating Effects on Intimate Partner Violence

Abstract: The links among social disorder, violence in the social support network (NIPV), community violence, and women's substance use were examined in a sample of 50 low-income, nonshelter women to predict intimate partner violence (IPV). The authors found that living in a neighborhood with higher levels of social disorder and using substances increased women's exposure to community violence that, in turn, was associated with increased rates of IPV. In addition, although not associated with community violence, NIPV wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
104
1
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(124 citation statements)
references
References 46 publications
10
104
1
8
Order By: Relevance
“…The finding that exposure to neighborhood violence was associated with an increase in recent male perpetration of IPV is consistent with previous studies 34,46,47 and supports the notion that "the environmental context influences what goes on in the privacy of homes." 46 , p. 396 One study 34 argued that the effect of community violence on male violence toward a female partner could be explicated by a lack of strong connections between community residents and hence, little collective efficacy to control the level of violence in their disordered neighborhoods.…”
Section: Discussionsupporting
confidence: 80%
“…The finding that exposure to neighborhood violence was associated with an increase in recent male perpetration of IPV is consistent with previous studies 34,46,47 and supports the notion that "the environmental context influences what goes on in the privacy of homes." 46 , p. 396 One study 34 argued that the effect of community violence on male violence toward a female partner could be explicated by a lack of strong connections between community residents and hence, little collective efficacy to control the level of violence in their disordered neighborhoods.…”
Section: Discussionsupporting
confidence: 80%
“…Overall, this finding supports the application of ecological models to describe the relationship between alcohol use and IPV as well as previous research that has identified an association between community-level social factors (e.g. neighborhood SES, community violence, and norms) and interpersonal violence (O'Campo et al 1995;Raghavan et al 2006;McKinney et al 2009;Raghavan et al 2009;Jain et al 2010;Robinson et al 2011;McKinney et al 2012;Chong et al 2015;Copp et al 2015;Graham et al 2017). To our knowledge, this is the first study to find an association between prevalence of alcohol use among partnered males and IPV, controlling for individual-level partner alcohol use in LMICs.…”
Section: Support For the Indirect And Direct Effect Modelssupporting
confidence: 88%
“…First, the inclusion of other relevant correlates of public responses to cases of IPVAW would help to further understand the processes involved in decision making leading to different types of responses to incidents of IPVAW. The inclusion of other possible predictors of public responses to IPVAW such as the influence of emotional factors, attitudes towards family privacy, victim-blaming attitudes, trust in the authorities' effectiveness, perception of the support available to victims, or contextual effects such as neighborhood social disorder would also help to better understand public responses to incidents of IPVAW (Christy & Voigt, 1994;Gracia & Herrero, 2007;Gracia, Herrero, Lila, & Fuente, 2009;Hadeed & El-Bassel, 2006;James, Johnson, & Raghavan, 2004;Levine, 1999;Raghavan, Mennerich, Sexton, & James, 2006;Weiner, 1980). Another potential limitation is that we used hypothetical scenarios as a stimulus rather than actual situations, and it is possible that public responses might differ from what they actually would do in a real situation (Fritzsche, Finkelstein, & Penner, 2000;Robinson & Chandek, 2000).…”
Section: Discussionmentioning
confidence: 99%